Application of Simplex Method with Exel Program (Solver) to Optimize Sales of Cabbage Chili - Abd. Kafi Al Madani; Irsadus Sholihah (Yayasan Adra Karima Hubbi, 2024)
In the world of trading, optimization problems include maximizing profits or minimizing costs, both of which can be solved using the simplex method. The purpose of this study is to maximize the profits of Mr. Sahri's cayenne pepper household production located in Sumber Anyar Village, Larangan Tokol, Tlanakan District, Pamekasan Regency. This study was conducted at Mr. Sahri's house as the owner of the cayenne pepper household industry. The analysis carried out in this study is an analysis using the simplex method with the Microsoft Excel solver function. The instruments used are observation and interviews. The results of the study indicate that the optimal production amount of each product (small, medium, large cayenne pepper) in Mr. Sahri's cayenne pepper household production so as to obtain maximum profit.